Vaccines. [edited by] Stanley A. Plotkin, Walter A. Orenstein, Paul A. Offit - Plotkin, Stanley A., 1932-; Orenstein, Walter A.; Offit, Paul A. (Elsevier Saunders, 2013)
This classic resource examines every aspect of vaccination - from development to use in reducing disease. In addition to in-depth chapters on individual vaccines, the book also covers many general topics such as immunology, public health and legal issues.